Urgensi yang Dialami Peserta Didik Sekolah Dasar dalam Literasi - Salsabilla, Tiara Dinda; Fitri, Yesinia; Ismayanti, Winda; Rahayu, Faras; Mahendra, Yozan Trio (Lembaga Yasin AlSys, 2023)
This study aims to determine the characteristics of reading difficulties experienced by students, including difficulty recognizing diphthongs, omitting letters, spelling haltingly, having a weakness in slurred speech (pelo) and students' low understanding of the contents of the reading. Reading is also one of the skills to get information which includes content and reading comprehension. The ability to read is very important for a student to have. Students' weaknesses in reading will affect students' self-confidence and cause students' learning motivation to be low. Based on the results of observations and interviews conducted with teachers and students, it was found that there were various characteristics of students' initial reading difficulties. First, the difficulty in recognizing letters. Characteristics of reading difficulties in the indicator of recognizing letters is difficulty identifying letters and making letters omitted. The omission of letters by students often occurs at the end of words